Studying the Effect of Experimental Bases on the Growth Quality of Liquid Nutritional Media for Submerged Cultivation of Plague Microbe Vaccine Strain - N. V. Abzaeva; S. E. Gostishcheva; O. L. Startseva; L. S. Katunina; D. A. Kovalev; G. F. Ivanova; A. V. Kostrominov; A. A. Kurilova (Проблемы особо опасных инфекций)
The aim of the study was to investigate the effect of experimental bases on the growth qualities of liquid nutrient media at the stage of obtaining the biomass of plague microbe vaccine strain using submerged cultivation.Materials and methods. Yersinia pestis EV NIIEG vaccine strain was used in the work. The cultivation was carried out in a 5 L bioreactor with automatic stirrer control. We used 28 variants of nutrient media obtained through combining five types of bases and six growth stimulants. Nutrient media without the addition of growth-stimulating additives were used as controls. The following parameters were assessed in the yield biomass: the total number of microbial cells, pH, the percentage of viable microbial cells.Results and discussion. On experimental nutrient media, biomasses of the plague microbe vaccine strain have been produced using submerged cultivation. After evaluating bacterial suspensions by the main indicators, the quality of the obtained suspensions has been compared depending on the nutrient medium used. The most promising bases identified are pancreatic hydrolyzate of casein with dry enzymatic peptone and acid hydrolyzate of corn syrup, especially in combination with such growth stimulants as sodium sulfite, ferrous ammonium sulfate or ammonium molybdate.